The impact of current failures on predicted well-being for future success: Different mechanisms of action in high and low self-threat situations - Hou, Zhijun; Wang, Yuting; Li, Lin; Song, Jingjing (Frontiers in Psychology, 2022)
This study explored the effect of current performance on the predicted well-being for future success and its mechanism. This empirical research consists of two experiments. In Study 1, the individual’s predicted well-being of future performance in the tests was lower in good feedback condition compared with bad feedback condition. It means that individuals have a higher expectation of future success after an unimportant loss. Study 2 focused on the moderating role of self-threat situations and the mediating role of affect and self-esteem in the effect of current performance feedback on predicted well-being. The results showed that individuals who got bad feedback have a low predicted well-being of future success only in a high self-threatening condition. Self-threat plays a moderating role between current performance and predicted well-being. The serial mediation role of affect and self-esteem in the negative effect of current performance on predicted well-being holds in high self-threat situations. By specifying the behavioral consequences and analyzing the psychological process in high and low self-threat situations, this research expands the literature on development of appropriate cognitive theories and propose novel measures and practical implications of enhancing predicted well-being.